2013
DOI: 10.1111/1365-2435.12084
|View full text |Cite
|
Sign up to set email alerts
|

Diet, development and the optimization of warning signals in post‐metamorphic green and black poison frogs

Abstract: Summary1. Many prey species are chemically defended and have conspicuous appearance to deter predators (i.e. aposematism). Such warning signals work because predators pay attention to the colour and size of signals, which they associate with unprofitability. 2. Paradoxically, in early life stages, aposematic species are often warningly coloured, but their chemical defences are lacking because they have yet to be acquired through the diet or synthesized endogenously. This state of being conspicuous yet poorly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 148 publications
(307 reference statements)
1
16
0
Order By: Relevance
“…Our study builds on the results of a previous paper, Flores et al. (), in which froglets with access to relatively little food appeared to simultaneously maximize both body size and signal luminance, while froglets with access to greater amounts of food, which were larger on average, reduced their investment in signal luminance as compared to smaller individuals. Here, we address the relative importance of body size and signal luminance as determinants of survival in the wild.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…Our study builds on the results of a previous paper, Flores et al. (), in which froglets with access to relatively little food appeared to simultaneously maximize both body size and signal luminance, while froglets with access to greater amounts of food, which were larger on average, reduced their investment in signal luminance as compared to smaller individuals. Here, we address the relative importance of body size and signal luminance as determinants of survival in the wild.…”
Section: Introductionsupporting
confidence: 63%
“…; Noonan and Comeault ), and similarly, experimental froglets did not show appreciable levels of UV reflectance in their dorsal skin (Flores et al. ). Accordingly, we found that the UV reflectance of our mixed clay was low (UV mixed clay ± SE: 0.077 ± 0.002, N = 10); therefore, it was unlikely to influence our results.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations